CONSTITUTIONAL MODEL OF RELIGIOUS RECOGNITION: A COMPARISON OF INDONESIA, AMERICA, GERMANY, MALAYSIA, IRAN, AND SAUDI ARABIA - Iman Pasu Marganda Hadiarto Purba; Thohir Luth; Tunggul Anshari Setia Negara; Nur Chanifah (KANUN:JURNAL ILMU HUKUM, 2026)
The recognition of religion by the state has prompted constitutional questions across diverse jurisdictions. This article analyzes the constitutional model of religious recognition in six countries, i.e. Indonesia, Germany, Malaysia, the United States, Iran, and Saudi Arabia. It adopts conceptual analysis and comparative constitutional law to conduct normative legal research. The primary materials consist of constitutions, laws, and regulations that govern state–religion relations. A functional comparative technique is employed to qualitatively examine the legal elements and their interconnections. The study’s findings show that models of religious recognition are shaped by the character of state–religion relations and by the legal systems each country adopts. No country presents an identical model of religious recognition, reflecting inherent structural differences in constitutional design. Constitutional forms of religious recognition are influenced by each country’s pattern of state–religion interaction, constitutional ideology, and legal tradition. There is no universal constitutional model of religious recognition that fits all contexts. Instead, each framework demonstrates how state ideology, legal culture, constitutional design, and the historical relationship between religion and the state converge to produce unique regimes.